Viral transmission in honey bees and native bees, supported by a global black queen cell virus phylogeny. (17th January 2019) - Murray, Elizabeth A.; Burand, John; Trikoz, Natalia; Schnabel, Julia; Grab, Heather; Danforth, Bryan N.
Summary: In recent decades, we have realized that honey bee viruses are not, in fact, exclusive to honey bees. The potential impact of Apis ‐affiliated viruses on native pollinators is prompting concern. Our research addresses the issue of virus crossover between honey bees and native bees foraging in the same localities. We measured the presence of black queen cell virus (BQCV), deformed wing virus (DWV) and sacbrood virus (SBV) in managed Apis mellifera (honey bees) and native Andrena spp. (subgenus Melandrena ) bee populations in five commercial orchards. We identified viral presence across sites and bees and related these data to measures of bee community diversity. All viruses were found in both managed and native bees, and BQCV was the most common virus in each. To establish evidence for viral crossover between taxa, we undertook an additional examination of BQCV where 74 samples were sequenced and placed in a global phylogenic framework of hundreds of BQCV strains. We demonstrate pathogen sharing across managed honey bees and distantly related wild bees. This phylogenetic analysis contributes to growing evidence for host switching and places local incidence patterns in a worldwide context, revealing multispecies viral transmission.